Unpacking the Emotional Dimension of Doctoral Supervision: Supervisors' Emotions and Emotion Regulation Strategies - Han, Ye; Xu, Yueting (Frontiers in Psychology, 2021)
Successful completion of a PhD is challenging for both the candidate and the supervisor. While doctoral students' emotional burdens received much attention, their supervisors' emotional experiences remain under-explored. Moreover, while teacher education research stressed the importance of teacher emotion regulation, empirical studies on doctoral supervisors' emotion regulation barely exist. The current qualitative study explored 17 computer science supervisors' emotions unfolding in doctoral supervision and their emotion regulation strategies. Semi-structured interviews revealed the supervisors' wide-ranging emotions, with their negative emotions more diverse and common than positive ones. The supervisors also regulated their emotions through multiple strategies within antecedent-focused and response-focused approaches. As one of the initial studies on doctoral supervisors' emotion and emotion regulation in their own right, the current study not only uncovers the complexity of the emotion-laden dimension of supervision, but also highlights the need for all stakeholders to attend to supervisors' psychological well-being in tandem with their students'.